(untitled) (Annals of Medical Research, 2021)
Aim: Toxoplasmosis caused by Toxoplasma gondii, is a zoonotic disease which is generally asymptomatic. However, it causes serious symptoms in pregnant women and immunocompromised individuals. About one third of the people worldwide are seropositive. Due to the civil war in Syria, Turkey has been home to more than 4 million refugees. This unexpected increase in the Syrian population in particular increases the risk of infectious diseases. The aim of this study was to evaluate the prevalence of Toxoplasma gondii, antitoxoplasma IgG and IgM antibodies in local and Syrian women, who were admitted to Obstetrics and Gynecology Clinic of Malatya Education and Research Hospital, which is a tertiary care hospital in eastern part of Turkey, between January 2015 and July 2019.Material and Methods: The anti-toxoplasma IgG and anti-toxoplasma IgM antibody values of women who were admitted to our hospital and evaluated in terms of toxoplasma, determined by using “Chemiluminescence Immunoassay (CLIA)” method, were investigated retrospectively.Results: According to the results analyzed in a total of 11.025 women, including 743 Syrian refugees, the seropositivity of antitoxoplasma IgG and IgM were found to be 25.8% (2.819/10.932) and 1.6% (180/11.025), respectively. Among these patients, the seropositivity of anti-toxoplasma IgG was found to be 25.3% (190/750) and the seropositivity of anti-toxoplasma IgM was found to be 2.5% (20/797) in pregnant women. Anti toxoplasma IgG and IgM seropositivity were found to be 27.9% and 0.5%, respectively, in Syrian women. In Malatya, a city located in eastern Turkey, Toxoplasma gondii seropositivity was found to be common to the extent that it could not be neglected in both local women and Syrian refugees. No statistically significant difference could be found in Syrian female refugees living in Malatya in terms of carrying toxoplasma antibodies when compared with the local women. More than 70% of pregnant women were observed to be seronegative and they were at serious risk for toxoplasmosis. In particular, it was concluded that women at childbearing age, who constitute the risk group, should be made aware of the disease and serological tests should be performed routinely for toxoplasma.